Uporaba logično mehkega krmiljenja za izboljšanje udobja vožnje vozil - Taskin, Yener (Strojniški vestnik, 2007)
In this study, a brand new fuzzy-logic method for the active suspension control of a vehicle is introduced. The method improves the ride comfort of passengers without losing any of the working space of the suspension. The derivative of the vehicle's vertical body displacement, the suspension deflection, and the combination of these variables were chosen as the inputs, and the actuator force was the output of the controller. This choice of input combination leads to a reduced rule base and a shorter computation time. The proposed controller is applied to a quarter-car model, and for the time responses different road conditions are considered in order to give a better understanding of the performance of the controller. Finally, the frequency responses are presented and the success of the proposed controller is discussed.
Keywords: mehka logika; vozila; načrtovanje; udobje; delovni prostor